UMP MyPerahu app empowers fishermens socioeconomic and ecotourism activities - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 7 September 2022 – A group of lecturers from the Faculty of Computing (FK), Universiti Malaysia Pahang (UMP) has developed the MyPerahu mobile app as one of the measures to empower socioeconomic and ecotourism in the fishing community.